E-WAQF based CP scorecard for sustainability: Firm & stakeholder perception - Ibrahim, Siti Sara; Mohd Noor, Abd Halim; Arshad, Roshayani (2017)
Purpose - Companies are currently paying increasing attention to sustainability due to greater expectations for corporations to be invested in the local community and environment instead of being solely concerned with profits. It has been our national agenda when the government itself, through the strategy paper issued by the Central Bank of Malaysia titled “Value-Based Intermediation (VBI): Strengthening the Roles and Impact of Islamic Finance in July 2017”, has proposing four (4) strategies, in which part of it has highlighted on the “effective and constructive collaboration with wider stakeholders, including those with no direct business relationships such as NGOs, societies and government”. Corporate Philanthropy (CP) was intended as a measure to execute this strategy, by displaying a company’s dedication to enhancing societal welfare through sharing corporate resources and applying discretionary business operations. However, existing research and preliminary surveys among stakeholders reveal that corporations are still creating unsustainable impact due to the habit of executing CP on a project-to-project basis (short-term).As such, a comprehensive e-scorecard is designed for a corporation, to strategically plan, implement and assess the performance of their CP activities.This e-scorecard is distributed as part of a pilot study to ascertain how well the e-scorecard system is embraced and utilized, based on the Technology Acceptance Model (TAM) through the evaluation on user’s perceived usefulness as well perceived ease-of-use toward e-scorecard . This research is beneficial to understand the needs of user towards the product in order to ensure a strategic collaborative is built between firm and stakeholder to solve socio-economic well being issues for sustainability.